KEGIATAN ZAKAT FITRAH PADA ANAK DIDIK RAUDHATUL ATHFAL DALAM PENGEMBANGAN KARAKTER ANAK - Rini, Asniar Fajar; Fauzi, Fauzi Fauzi (Jurnal Golden Age, 2023)
Zakat fitrah is a mandatory alms given during the month of Ramadan until Eid Al-Fitr, which can be given in the form of rice or staple food equivalent to 2.5 kilograms per person. The collection and distribution of zakat fitrah at early childhood education institutions, especially at Raudhatul Athfal Masyithoh 13 Sokaraja Lor, is held every year as a form of implementation of curiculum of Islamic Religious Education in order to foster character in students. The formation of characters that appear in children will be very diverse. This study intends to explain the practice of zakat fitrah conducted by RA Masyithoh 13 Sokaraja which will foster various characters in children. This research is a  qualitative research with case study method. The results of the research led to good children's character, namely raising social care attitudes and wanting to share with others.Keywords: Zakat Fitrah, RA's Students, Children's Character